The role of oxidative stress in male infertility: connection to sperm telomere shortening and overall DNA damage - Glišić, Biljana; Kotur Stevuljević, Jelena (Archives of Pharmacy, 2025)
Male infertility affects approximately 20% of men, with 30–40% of cases being linked to issues in both partners. While sperm production may be normal, DNA damage in spermatozoa can occur and become a primary cause of infertility. The exacerbation of oxidative stress leads to damage to various biomolecules, such as DNA fragmentation, lipid peroxidation, and protein oxidation, all of which can impair egg fertilization and embryo development. Elevated levels of reactive oxygen species (ROS) in semen are associated with poor sperm quality, reduced fertilization potential, and increased sperm DNA fragmentation. Additionally, shorter telomeres in semen correlate with reduced sperm vitality and function. Oxidative stress accelerates telomere attrition by inducing DNA damage, which leads to telomere shortening and potentially compromises sperm function and fertility. DNA damage can occur at different stages of spermatogenesis and fertilization. If the damage surpasses the oocyte’s repair capacity, infertility may occur. Various tests are available to assess sperm DNA damage, with the sperm DNA fragmentation (SDF) test being one of the most promising. DNA damage is quantified as the DNA fragmentation index (DFI), which represents the percentage of spermatozoa with fragmented DNA. Although reference intervals for DFI may vary depending on the method used, DFI ≤ 15% is generally considered normal, 15–30% is considered average, and DFI ≥ 30% indicates poor DNA integrity, which may negatively impact pregnancy outcomes.